Pharmacological analysis of cyclooxygenase-1 in inflammation - Smith, Christopher J. (The National Academy of Sciences, 1998)
The enzymes cyclooxygenase-1 and cyclooxygenase-2 (COX-1 and COX-2) catalyze the conversion of arachidonic acid to prostaglandin (PG) H(2), the precursor of PGs and thromboxane. These lipid mediators play important roles in inflammation and pain and in normal physiological functions. While there are abundant data indicating that the inducible isoform, COX-2, is important in inflammation and pain, the constitutively expressed isoform, COX-1, has also been suggested to play a role in inflammatory processes. To address the latter question pharmacologically, we used a highly selective COX-1 inhibitor, SC-560 (COX-1 IC(50) = 0.009 μM; COX-2 IC(50) = 6.3 μM). SC-560 inhibited COX-1-derived platelet thromboxane B(2), gastric PGE(2), and dermal PGE(2) production, indicating that it was orally active, but did not inhibit COX-2-derived PGs in the lipopolysaccharide-induced rat air pouch. Therapeutic or prophylactic administration of SC-560 in the rat carrageenan footpad model did not affect acute inflammation or hyperalgesia at doses that markedly inhibited in vivo COX-1 activity. By contrast, celecoxib, a selective COX-2 inhibitor, was anti-inflammatory and analgesic in this model. Paradoxically, both SC-560 and celecoxib reduced paw PGs to equivalent levels. Increased levels of PGs were found in the cerebrospinal fluid after carrageenan injection and were markedly reduced by celecoxib, but were not affected by SC-560. These results suggest that, in addition to the role of peripherally produced PGs, there is a critical, centrally mediated neurological component to inflammatory pain that is mediated at least in part by COX-2.